Control of Rectification and Gating of Cloned K(ATP) Channels by the Kir6.2 Subunit - Shyng, S.-L. (The Rockefeller University Press, 1997)
K(ATP) channels are a functional complex of sulphonylurea receptor (SUR1, SUR2) and inward rectifier K(+) (Kir6.1, Kir6.2) channel subunits. We have studied the role of the putative pore forming subunit (Kir6.2) in regulation of rectification and gating of K(ATP) channels generated by transfection of SUR1 and Kir6.2 cDNAs in COSm6 cells. In the absence of internal polyvalent cations, the current-voltage relationship is sigmoidal. Mg(2+) or spermine(4+) (spm) each induces a mild inward rectification. Mutation of the asparagine at position 160 in Kir6.2 to aspartate (N160D) or glutamate (N160E) increases the degree of rectification induced by Mg(2+) or spermine(4+), whereas wild-type rectification is still observed after mutation to other neutral residues (alanine–N160A, glutamine–N160Q). These results are consistent with this residue lining the pore of the channel and contributing to the binding of these cations, as demonstrated for the equivalent site in homomeric ROMK1 (Kir1.1) channels. Since Kir6.2 contains no consensus ATP binding site, whereas SUR1 does, inhibition by ATP has been assumed to depend on interactions with SUR1. However, we found that the [ATP] causing half-maximal inhibition of current (K (i)) was affected by mutation of N160. Channels formed from N160D or N160Q mutant subunits had lower apparent sensitivity to ATP (K (i,N160D) = 46.1 μM; K (i,N160Q) = 62.9 μM) than wild-type, N160E, or N160A channels (K (i) = 10.4, 17.7, 6.4 μM, respectively). This might suggest that ATP binding to the channel complex was altered, although examination of channel open probabilities indicates instead that the residue at position 160 alters the ATP-independent open probability, i.e., it controls the free energy of the open state, thereby affecting the “coupling” of ATP binding to channel inhibition. The results can be interpreted in terms of a kinetic scheme whereby the residue at Kir6.2 position 160 controls the rate constants governing transitions to and from the open state, without directly affecting ATP binding or unbinding transitions.